PERSENTASE TUTUPAN KARANG DI PERAIRAN MAMBURIT DAN PERAIRAN SAPAPAN KABUPATEN SUMENEP PROVINSI JAWA TIMUR - Sawiya Sawiya; Abdul Muqsith (Samakia : Jurnal Ilmu Perikanan, 2015)
This study aimed to know the percent of coral reefs in the waters closing Mamburit and Water Sapapan Sumenep Regency East Java province, carried out in April 2013. The method used was Line Intercept Transect at a depth of 3 meters and 10 meters in the area Winward and leeward. The results showed that the percentage of coral cover in the area Mamburit Bodies Winward depth of 3 m = 34.13% and a depth of 10 m = 87.94%, while for the leeward areas a depth of 3 m = 80.87% and a depth of 10 m = 52.22 %. Pebutupan percentage of coral reefs in the waters of the region Sapapan Winward depth of 3 m, = 55.09% and a depth of 10 m = 27.65%, while in the leeward areas a depth of 3 m, the percentage of coral cover = 42.03% and a depth of 10 m = 37.3%. Physical conditions in the waters Mamburit strongly supports the growth of coral reefs as well as in the waters Sapapan.